Action relationships concatenate representations of separate objects in the ventral visual system. - Roberts, K; Humphreys, G (2010)
Objects in the real world are encountered in contexts where they interact together. Though it is known that neurons in the ventral visual stream mediate the recognition of individual objects, we have minimal knowledge of how multiple objects are processed at a neural level. We examined the neural response to pairs of objects using functional magnetic resonance imaging (fMRI). Objects positioned to interact together activated bilateral lateral occipital complex (LOC) and fusiform gyrus. This occurred irrespective of whether the objects were attended. In LOC, the effect of positioning objects for action was found regardless of whether the objects formed a familiar or unfamiliar action pair. In the fusiform gyrus activation was found when objects formed a familiar action pair. No changes were apparent in visuomotor (premotor and parietal) regions which might reflect a motor-based response to objects. These results show that ventral-stream regions respond to the interaction between objects, as well as to the sensory and functional properties of individual objects.